T-bet is rapidly induced by interferon-γ in lymphoid and myeloid cells - Lighvani, Andre A. (The National Academy of Sciences, 2001)
Differentiation of naive CD4(+) T cells into IFN-γ-producing T helper 1 (T(H)1) cells is pivotal for protective immune responses against intracellular pathogens. T-bet, a recently discovered member of the T-box transcription factor family, has been reported to play a critical role in this process, promoting IFN-γ production. Although terminal T(H)1 differentiation occurs over days, we now show that challenge of mice with a prototypical T(H)1-inducing stimulus, Toxoplasma gondii soluble extract, rapidly induced IFN-γ and T-bet; T-bet induction was substantially lower in IFN-γ-deficient mice. Naive T cells expressed little T-bet, but this transcription factor was induced markedly by the combination of IFN-γ and cognate antigen. Human myeloid antigen-presenting cells showed T-bet induction after IFN-γ stimulation alone, and this induction was antagonized by IL-4 and granulocyte/macrophage colony-stimulating factor. Although T-bet was induced rapidly and directly by IFN-γ, it was not induced by IFN-α, lipopolysaccharide, or IL-1, indicating that this action of IFN-γ was specific. Moreover, T-bet induction was dependent on Stat1 but not Stat4. These data argue for a model in which IFN-γ gene regulation involves an autocrine loop, whereby the cytokine regulates a transcription factor that promotes its own production. These findings substantially alter the current view of T-bet in IFN-γ regulation and promotion of cell-mediated immune responses.